(untitled) (International Journal of Engineering and Computer Science, 2015)
When storage of the data in necessary over cloud data integrity verification is one of the biggest security issue . Provable data possession is one of the method available for checking the integrity of data. In this paper, we have concentrated on the creation of an efficient PDP method for distributed cloud storage, in which we consider the existence of multiple cloud service providers maintaining and storing client’s data in cooperative manner. This cooperatively working PDP method is based on indexing hierarchy & homomorphic variable response method. We show the security of our scheme based on trusted third party and zero-awareness proof structure, which can fulfill reliability of awareness, completeness, and properties.